DURABILITY AND RELIABILITY ANALYSIS OF UNDERGROUND PIPELINE INSTALLATION IN THE CITY - , Л. И., М. В. (Municipal economy of cities. Series: «Economy science», 2013)
The main parameters of the reliability of pipelines, assess their impact on the duration of use and the ability to predict the crash. The main factors used in assessing the reliability of the components and system utilities.